Utility and limitations of EEG in the diagnosis and management of ALDH7A1-related pyridoxine-dependent epilepsy. A retrospective observational study - Arntsen, Vibeke; Jamali, Ahmed; Sikiric, Alma; Kristensen, Erle; Tangeraas, Trine; Kupliauskiene, Guste; Stefansdottir, Sigurbjörg; Bindoff, Laurence A.; Sand, Trond; Brodtkorb, Eylert (Frontiers in Neurology, 2024)
Purpose Pyridoxine-dependent epilepsy due to ALDH7A1 variants (PDE-ALDH7A1) is a rare disorder, presenting typically with severe neonatal, epileptic encephalopathy. Early diagnosis is imperative to prevent uncontrolled seizures. We have explored the role of EEG in the diagnosis and management of PDE. Methods A total of 13 Norwegian patients with PDE-ALDH7A1 were identified, of whom five had reached adult age. Altogether 163 EEG recordings were assessed, 101 from the 1st year of life. Results Median age at seizure onset was 9 h (IQR 41), range 1 h-6 days. Median delay from first seizure to first pyridoxine injection was 2 days (IQR 5.5). An EEG burst suppression pattern was seen in eight patients (62%) during the first 5 days of life. Eleven patients had recordings during pyridoxine injections: in three, immediate EEG improvement correlated with seizure control, whereas in six, no change of epileptiform activity occurred. Of these six, one had prompt clinical effect, one had delayed effect (< 1 day), one had no effect, one had uncertain effect, and another had more seizures. A patient without seizures at time of pyridoxine trial remained seizure free for 6 days. Two patients with prompt clinical effect had increased paroxysmal activity, one as a conversion to burst suppression. Autonomic seizures in the form of apnoea appeared to promote respiratory distress and were documented by EEG in one patient. EEG follow-up in adult age did not show signs of progressing encephalopathy. Conclusion A neonatal burst suppression EEG pattern should raise the suspicion of PDE-ALDH7A1. Respiratory distress is common; isolated apnoeic seizures may contribute. EEG responses during pyridoxine trials are diverse, often with poor correlation to immediate clinical effect. Reliance on single trials may lead to under-recognition of this treatable condition. Pyridoxine should be continued until results from biomarkers and genetic testing are available.